Analisis Kepuasan Dosen Terhadap Layanan Akademik Fakultas Keguruan dan Ilmu Pendidikan Universitas X - Esti Harini; Irham Taufiq (LP2M Universitas Sarjanawiyata Tamansiswa, 2020)
The aim of this research was to know some academic service satisfaction problem to FKIP lecturers.Â The population of this research was active lecturer of FKIP UNIVERSITAS X at the 2019/2020 academic year. Samples were taken 10% of the population. The research design used was descriptive quantitative research through populative observations from FKIP UNIVERSITAS X lecturers. Questionnaire for the satisfaction of lecturer academic services at FKIP UNIVERSITAS X is worthy of use. Feasibility can be seen from the results of material validation. Material expert validation was carried out by material experts namely SPMF and GMP. The average score for the material is 3.6 and is included in good criteria. The tendency of lecturer satisfaction level on service quality in FKIP UNIVERSITAS X is in the quite satisfied category. and satisfaction level tendency for each aspect, 6 aspects in the category are quite satisfied.